Deglobalization 2016-2021: A Systematic Literature Review - Gordon, Tristan Michael (Auckland University of Technology, 2023)
Deglobalization is the process which results in the breaking down of global interconnection and interdependence. It refers to the undoing of globalization. This research project investigated how different factors, trends, issues and developments have affected deglobalization over the last five years thus helping to determine the trajectory of the deglobalization phenomenon. These factors include job insecurities, wage stagnation, wealth inequality, nationalism and global economic shocks. This research used a systematic literature review for data collection and thematic analysis for data analysis. The systematic literature review collected 52 articles for examination. Each article was read in its entirety and coded through the thematic analysis process. Through this process five themes emerged, each capturing an argument being made about the future of deglobalization. The five themes were Sustained Globalization which argues that globalization will continue, Decreased Globalization which argues globalization will continue but with a reduced level of international activity, Isolated Deglobalization which argues that deglobalization will manifest itself but only within vulnerable nations, Widespread Deglobalization which argues that deglobalization will manifest globally, and Restructured Global Order which argues the world is experiencing a reconfiguration of the international structure that facilitates global interconnection. The findings point to how factors such as automation adoption, long-term wealth inequality, poor distribution of globalization benefits, rising nationalism, global hegemonic decline and the COVID-19 pandemic have affected the deglobalization phenomenon over the last five years. This research found the world is shifting toward a state of deglobalization at an accelerated rate. However, this path is not a certainty as there are key events that may alter the course of deglobalization such as the result of the 2024 U.S.A presidential elections, the outcome of the Ukraine-Russian War and the success of Chinese initiatives to further globalization.